Enhanced creative thinking under dopaminergic therapy in Parkinson disease. Issue 6 (10th June 2014) - Faust‐Socher, Achinoam; Kenett, Yoed N.; Cohen, Oren S.; Hassin‐Baer, Sharon; Inzelberg, Rivka
<x xml:space="preserve">Abstract</x> Objective Creative thinking requires a combination of originality, flexibility, and usefulness. Several reports described enhanced artistic creativity in Parkinson disease (PD) patients treated with dopaminergic agents. We aimed to examine PD patients' ability to perform creativity tasks compared to healthy controls and to verify whether creativity is related to an impulse control disorder (ICD) as a complication of dopaminergic therapy. Methods Right‐handed PD patients treated with dopamine agonists and/or levodopa, and age‐ and education‐ matched neurologically healthy controls were assessed using the Montreal Cognitive Assessment, semantic verbal fluency, Beck Depression Inventory, and Questionnaire for Impulsive–Compulsive Disorders in Parkinson Disease Rating Scale (QUIP‐RS). Creativity assessment included Comprehension of Novel Metaphors (CNM), Remote Association Test, and Tel Aviv Creativity Test (TACT). Groups were compared using analyses of variance, t tests, and correlation analyses. Results Twenty‐seven PD patients (age, mean ± standard deviation = 62 ± 7 years; education = 16 ± 3 years; disease duration = 5.8 ± 3.9 years) and 27 controls (age = 59 ± 9 years; education 17 ± 3 years) participated. PD patients performed significantly better than controls in divergent thinking tasks; specifically, the TACT‐Visual for both fluency (33.48 ± 11.83 vs 25.59 ± 10.27, p = 0.034) and quality (15.78 ± 7.6 vs 11.19 ± 6.22, p = 0.025). Comprehension of Novel Metaphors was better in PD patients vs controls (0.71 ± 0.23 vs 0.55 ± 0.29, p = 0.04). QUIP‐RS scores did not correlate with creativity measures. Interpretation PD patients treated with dopaminergic drugs demonstrated enhanced verbal and visual creativity as compared to neurologically healthy controls. This feature was unrelated to ICD. Dopaminergic agents might act through the reduction of latent inhibition, resulting in widening of the associative network and enriched divergent thinking. Ann Neurol 2014;75:935–942